Not Always More Trees Means More Water - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2011)
For many decades, concerned by the undeniable deforestation data, environmental management has included re-vegetation activities in unforested areas intended to (re)create a forest environment.